Gender, hypertension duration, and self-management behavior in adult patients - Ayuk Cucuk Iskandar; Fitriani Fitriani (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Self-management behavior plays an important role in controlling hypertension and preventing complications. Evidence in the adult population still needs to be strengthened regarding sociodemographic factors such as gender and the duration of having hypertension in influencing variations in self-management behavior. Purpose: To analyze the correlation between gender and duration of hypertension with self-management behavior in adult patients with hypertension. Method: This quantitative study uses a cross-sectional analytical approach, involving 287 adult patients with hypertension registered at six primary healthcare facilities on Tarakan Island, using quota sampling techniques. Data on respondent characteristics, including age, gender, and duration of hypertension, were collected using a general demographic characteristics questionnaire, while self-management behavior was measured using the Hypertension Self-Management Behaviors Questionnaire. Data analysis to determine correlation using the chi-square statistical test, with a significance level of p<0.05. Results: The majority of respondents are female, and more than half have had hypertension £ 3 years. There is a significant correlation between gender and self-management behavior (p=<0.001), with the majority of women exhibiting moderate self-management behavior. Conversely, no significant relationship was identified between the duration of hypertension and self-management behavior (p=0.150). Conclusions: There is a significant relationship between gender and self-management behavior, indicating that gender differences contribute to chronic disease management behavior, particularly in hypertension. Furthermore, the non-significance of the duration of hypertension indicates that the length of illness is not always accompanied by improved self-management behaviors. Nurses and other health professionals need to consider gender differences when designing education and support programs to optimize self-management behaviors in adult patients with hypertension.